Produ????o mais limpa: estudo de casos m??ltiplos em padarias de Recife - Souza, ??llen Fernanda Gomes de (2016)
The Cleaner Production is an environmental tool, that, when deployed, results in many benefits. This tool is aligned to the dynamic balance of sustainable development, they are: environmental, economic and social. The objective of this research is to analyze the implementation of the Cleaner Production developed by bakeries in Recife suggested by Ecop??o project. This project was developed by Sebrae-PE to align sustainability at the bakeries of Recife, through the tool of the Cleaner Production. The literature review was based on key search terms, such as sustainable development, Cleaner Production and family businesses. The methodology of this study is qualitative in nature. The bakery sector is between the six major industries of the country. In 2014 the sector generated a turnover of R$ 8.5 billion. Six bakeries in Recife, that implemented the project, were studyed. It developed a multiple case study with the documentary analysis of Ecop??o project reports, direct observation, interviews with responsible for the creation of the project and with the owners of the six surveyed bakeries. The interviews followed a semi-structured script and were recorded and transcribed for analysis of results. The analysis was based on the method of triangulation and synthesis of crossed cases. According to the actions suggested by Ecop??o project bakery 2 was the one that held the shares. Since it implemented a new power plant and the actions have been implemented with the help of a consultant. The bakery 4 was the least accomplished actions. Due to problems with its facilities and staff. By the results of the bakeries studied the implementation of Ecop??o project actions related to Cleaner Production is an excellent contribution tool for better sustainable development in this sector.